(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This study sheds the light on determining the correlation between mental arithmetic ability and working visual memory, and the sample of the study members consisted of 368 male and female pupils from private schools affiliated to the General Directorate of Education in Babylon In order to achieve the objectives of the current research, it was necessary to have a test to measure mental arithmetic for primary school pupils, and given the absence of a local or Arabic test within the limits of the researcher’s knowledge, she decided to prepare a test in mental arithmetic consisting of five parts, four of which are related to numerical issues and a special part to verbal issues and to define the concept of arithmetic The researcher adopted the Reys 1993 study (Reys, 1993). Where the first part consists of the skill of addition and contains four paragraphs, the second part is related to the skill of subtraction and contains four paragraphs, the third part is related to the skill of multiplication and contains five paragraphs, the fourth part is concerned with the skill of division and contains five paragraphs, as for the fifth part, this part is specific to verbal skills and contains It is divided into four paragraphs distributed over the four arithmetic operations (addition, subtraction, multiplication, division), and thus the test paragraphs are (22) items. As for the working visual memory test. The test consists of (40) paragraphs in its final form, where the paragraphs are in the form of optical slides, and the first slides begin with two components in each slide, then gradually progress until they become (5-6) components. All are simple black and white shapes. The test can be applied individually or collectively, and in the case of applying the test in an individual way, it is possible to display the test on a computer and statistical analysis of the two test paragraphs was conducted and conclusions were reached on the basis of which a set of proposals and recommendations were developed